AI-BASED LEARNING MANAGEMENT: THE INFLUENCE OF THE USE OF AI AND LEARNING ORGANIZATION ON STUDENT LEARNING INNOVATION - Khoirinnisa Khoirinnisa; Munirul Abidin (Jurnal Manajemen Pendidikan, 2026)
The transformation of higher education in the era of the Industrial Revolution 4.0 and Society 5.0 requires institutions to integrate technology and build adaptive learning ecosystems. One of the technologies that is increasingly used is Artificial Intelligence (AI), which is able to personalize the learning experience and increase learning effectiveness. On the other hand, the application of the concept of learning organization is believed to strengthen collaboration, creativity, and adaptability in the academic environment. This study aims to analyze the influence of the use of AI and learning organization on student learning innovation, both partially and simultaneously. The research method used is a quantitative approach with survey techniques. The research sample consisted of 118 active students in semesters 4–8 who had used an AI-based learning platform for at least one semester. The research instrument was a Likert scale closed questionnaire, which was analyzed using multiple linear regression with the help of SPSS 26. The results of the study show that (1) the use of AI has a positive and significant effect on student learning innovation; (2) learning organization has also been proven to have a significant influence on learning innovation; and (3) the simultaneous use of AI and learning organization has a significant influence on student learning innovation. However, the R Square value of 0.112 indicates that there are still other factors outside of this study that also affect learning innovation.